Taxation under Direct Democracy - Stephan Geschwind; Felix Roesel (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Do citizens legislate different tax policies than parliaments? We provide quasi-experimental evidence for causal effects of direct democracy. Town meetings (popular assemblies) replace local councils in small German municipalities below a specific population threshold. Difference-in-differences, RD and event study estimates consistently show that direct democracy comes with sizable but selective tax cuts. Property tax rates, which apply to all residents, decrease by some 10 to 15% under direct democracy. We do not find that business tax rates change. Direct democracy allows citizens to design tax policies more individually than voting for a high-tax or low-tax party in elections.
Keywords: D71; D72; H71; R51; 330; direct democracy; town meeting; popular assembly; constitution; public finance; taxation